Three-dimensional confocal morphometry reveals structural changes in astrocyte morphology in situ - Chvátal, Alexandr; Anderová, Miroslava; Hock, Miroslav; Prajerová, Iva; Neprasová, Helena; Chvátal, Viktor; Kirchhoff, Frank; Syková, Eva (Journal of neuroscience research, 2007)
Neuronal activity and many pathological states in the CNS are accompanied by transient astrocytic swelling, which affects excitability, extrasynaptic transmission, and neuron-glia interactions. By using three-dimensional confocal morphometry (3DCM), we quantified the morphometric parameters of astrocytes in intact tissue. In experiments performed in brain cortex slices from transgenic GFAP/EGFP mice, we applied 3DCM to study the dynamic changes in astrocyte morphology during hypotonic stress. Our morphometric analysis showed that the effect of a 10-min application of hypotonic solution (200 mmol/kg) on the swelling of different cell compartments was dependent on the extent of the swelling of the total astrocyte volume. If the swelling of the whole cell, i.e., soma and processes, was less than approximately 10%, there were no differences between the swelling of the soma and the processes. However, if the swelling of the total cell volume was greater than 10%, the swelling of the processes was greater than the swelling of the soma. Analyzing the effect of hypotonic solution on the morphology of these astrocytes revealed that the total cell volume increased; however, certain cell compartments were distinguished in which the volume increased, whereas in other compartments cell volume decreased or apparently did not change, and the structure of some compartments was altered. Our data show that astrocytes in brain slices undergoing hypotonic stress display cell volume regulation as well as transient changes in morphology.
Keywords: Animals; myši transgenní; Green Fluorescent Proteins; astrocyty; zobrazování trojrozměrné; Imaging, Three-Dimensional; Mice, Transgenic; Glial Fibrillary Acidic Protein; hypotonické roztoky; Mice; Organ Culture Techniques; mozek; myši; Astrocytes; zelené fluorescenční proteiny; orgánové kultury - kultivační techniky; gliový fibrilární kyselý protein; Hypotonic Solutions; počítačové zpracování obrazu; Brain; promotorové oblasti (genetika); zvířata; Microscopy, Confocal; konfokální mikroskopie; Promoter Regions, Genetic; Image Processing, Computer-Assisted